Pemanfaatan Perpustakaan sebagai Sumber Belajar oleh Mahasiswa Program Studi Pendidikan Ekonomi - Basyirun, Fajri; Ilyas, M (Jurusan PIPS FKIP UMMY Solok, 2021)
This research aims to determine the activities of students of the Economic Education Study Program in utilizing of the Mahaputra Muhammad Yamin University library as a learning resource, obtaining information and analyzing what information materials can be obtained from the Mahaputra Muhammad Yamin University library, and obtaining information regarding the obstacles faced by students in utilizing the library at Mahaputra Muhammad Yamin University as a learning resource. This research is a qualitative research in which the research data is obtained through interviews. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results of the study found that students have used the library as a learning resource by borrowing reference books, doing group study, and utilizing the available internet wifi. The information obtained in the library is in the form of reference books for lecture assignments and the preparation of final assignments, then also available novels, magazines, story books and student final assignments. The constraints found in utilizing the library are still the lack of availability of references that are sought both in terms of collection and quantity and there are also no results of research and community service produced by lecturers at the Mahaputra Muhammad Yamin University library.